Crisis Management in the Brazilian Franchising Sector During the Covid-19 Pandemic - Thelma Valéria Rocha; Vanessa P. G. Bretas; Márcio Fonseca; Cássia Aparecida Pizani; Angela Satiko Yojo (Internext: Revista Eletrônica de Negócios Internacionais, 2022)
Objective: The objective of the article is to analyse the effects of the Covid-19 pandemic on the Brazilian franchise sector and to identify the main strategies adopted by companies to mitigate the negative impacts of the crisis.